2019
DOI: 10.1371/journal.pone.0215967
|View full text |Cite
|
Sign up to set email alerts
|

Time to acute kidney injury and its predictors among newly diagnosed Type 2 diabetic patients at government hospitals in Harari Region, East Ethiopia

Abstract: Background Incidence of Acute Kidney Injury (AKI) among Type 2 diabetic patients is significantly increasing. But, earlier studies has focused on the admitted patients which may hide the true nature of the Acute Kidney Injury among Type 2 Diabetic (T2D) patients. So, this study was conducted to determine the time to Acute Kidney Injury and its predictors among Type 2 Diabetic patients in Harari Region, East Ethiopia. Methods We conducted a retrospective cohort study amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 28 publications
4
22
2
Order By: Relevance
“…During full-text screening, 113 studies were excluded for failing to provide qualified endpoints or complete data for our meta-analysis. Therefore, a total of 18 studies [ 11–13 , 15–29 ] that included 38991 patients were ultimately included in the current meta-analysis to evaluate the role of PA in DN patients.…”
Section: Resultsmentioning
confidence: 99%
“…During full-text screening, 113 studies were excluded for failing to provide qualified endpoints or complete data for our meta-analysis. Therefore, a total of 18 studies [ 11–13 , 15–29 ] that included 38991 patients were ultimately included in the current meta-analysis to evaluate the role of PA in DN patients.…”
Section: Resultsmentioning
confidence: 99%
“…27 BMI: A person was classified as underweight (BMI < 18.5 kg/m 2 ), normal body weight (BMI 18.5−24.9 kg/ m 2 ), overweight (BMI 25-29.9 kg/m 2 ), or obese (BMI ≥ 30 kg/m 2 ). [28][29][30] Smoking: Currently smoking is smoking a cigarette at least once within the last 30 days. 16,24 Drinking alcohol: Patients were classified as drinking alcohol if they had a history of consuming an alcoholic drink since the last visit.…”
Section: Operational Definitionsmentioning
confidence: 99%
“…10 In a retrospective follow-up study conducted in Harari Region, East Ethiopia, from 2013 to 2017, the total incidence rate of AKI among type 2 DM patients was 14.5%. 11 Many studies suggested that the predictors of AKI among type 2 DM patients are old age, congestive heart failure (CHF), chronic kidney disease (CKD), hypertension (HTN), smoking, alcohol consumption, diabetic nephropathy (DN), infections, aminoglycosides, diabetic ketoacidosis, non-steroidal anti-inflammatory drugs (NSAIDs), long duration of DM, diuretics and betablockers and delay of follow-up. 5 Acute kidney injury is common and its burden has risen over the last two decades among type 2 DM patients.…”
Section: Introductionmentioning
confidence: 99%